Educational Gender Inequality in Sub-Saharan Africa: A Long-term Perspective - Joerg Baten; Michiel de Haas; Elisabeth Kempter; Felix Meier zu Selhausen (African Economic History Network (AEHN), 2020)
To what extent was the 20th century schooling revolution in sub-Saharan Africa shared equally between men and women? We examine trajectories of educational gender inequality over the 20th century, using census data from 21 African countries and applying a birth-cohort approach. We present three sets of findings. First, compared to other developing regions with similar histories of colonial rule and educational expansion, sub-Saharan Africa performed comparatively poorly in closing educational gender gaps (M-F) and gender ratios (M/F) over the 20th century. Second, in most African countries, the educational gender gap rose during the colonial era, peaked mid-century, and declined, albeit at very different rates, after independence. Southern African countries were remarkably gender equal, both in terms of gaps and ratios. French (former) colonies had smaller gaps but higher ratios than British (former) colonies, which we attribute to slower expansion of male education in the former. Both on the world-region and country-level, the expansion of male education is associated initially with a growing gender gap, and subsequently a decline. We refer to this pattern as the "educational gender Kuznets curve". Third, using data from 6 decadal cohorts across 1,177 African regions, we explore sub-national correlates of educational gender equity. Better connected and urban regions witnessed lower educational gender inequality. In regions with large Christian mission stations in the early 20th century access to education was also less gender unequal, an effect that persisted into the post-colonial period. We also find that during the colonial era, cash crop cultivation was not consistently associated with larger gender gaps, while female farming systems were associated with smaller gaps. The sub-national cross-sectional results confirm the existence of an educational gender Kuznets curve.
Keywords: I24; J16; N37; N97; Z12; 330; Education; Gender Inequality; Africa; Long-Term Development; Colonialism; Missions